Technical Characteristics of the Ovation Alto for the Treatment of Abdominal Aortic Aneurysms: Application to Challenging Anatomies - Georgakarakos, Efstratios; Dimitriadis, Konstantinos; Argyriou, Christos; Efenti, Gioultzan Memet; Doukas, Damianos; Georgiadis, George S. (AORTA, 2023)
The Ovation Alto design repositions the maximum diameter of the proximal sealing ring at 7 mm below the lowermost renal artery. Although it has been introduced to address abdominal aortic aneurysms with short necks ≥7 mm, we present further applications of Alto in other neck irregularities, presenting four representative challenging cases with a short, wide, and conical neck, as well a juxtarenal aneurysm. At 1-month follow-up, there was 100% technical and clinical success.
Keywords: Ovation Alto; abdominal aortic aneurysm; endovascular aneurysm repair; wide neck; juxtarenal aneurysm